Time-Driven, Activity-Based Costing of Presurgical Infant Orthopedics: A Critical Component of Establishing Value of Latham Appliance and Nasoalveolar Molding. Issue 3 (23rd February 2021) - Ganske, Ingrid M.; Sanchez, Karl; Le, Elliot; Langa, Olivia C.; Sharif-Askary, Banafsheh; Ross, Elizabeth; Santiago, Pedro; Meara, John G.; Padwa, Bonnie L.; Allori, Alexander C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Value-based health-care reform requires assessment of outcomes and costs of medical interventions. In cleft care, presurgical infant orthopedics is still being evaluated for clinical benefits and risks; however, the cost of these procedures has been largely ignored. This study uses robust accounting methods to quantify the cost of providing two types of presurgical infant orthopedics: Latham appliance treatment and nasoalveolar molding. Methods: This is a prospective study of patients with nonsyndromic cleft lip and/or palate who underwent treatment with presurgical infant orthopedics from 2017 to 2019 at two academic centers. Costs were measured using time-driven activity-based costing. Personnel costs, facility costs (operating room, clinic, and inpatient ward), and equipment costs were included. Travel expenses were incorporated as an estimate of direct costs borne by the family, but indirect costs (e.g., time off from work) were not considered. Results: Twenty-three patients were treated with Latham appliance treatment and 14 were treated with nasoalveolar molding. For Latham appliance treatment, average total cost was $7553 per patient ($1041 for personnel, $637 for equipment, $4871 for facility, and $1004 for travel over 6.5 visits). Unilateral and bilateral costs were $6891 and $8860, respectively. For nasoalveolar molding, average cost totaled $2541 ($364 for personnel, $151 for equipment, $300 for facility, and $1726 for travel over 13 visits); $2120 for unilateral and $3048 for bilateral treatment. Conclusions: The major difference in cost is attributable to operative placement of the Latham device. Travel cost for nasoalveolar molding is often higher because of frequent clinical encounters required. Future investigation should focus on whether outcomes achieved by presurgical infant orthopedics justify the $2100 to $8900 expenditure for these adjunctive procedures.